Noiseless Variable-Pressure Neck Chamber Device to Assess the Carotid Baroreflex Function - Pinheiro, Alessandro; Vianna, Lauro C.; Carmo, Jake C. (Frontiers in Physiology, 2021)
Background: The blood pressure responses to baroreflex perturbations can be assessed only using the variable-pressure neck chamber technique. However, the application of this approach in hospital environments is limited owing to the loud noise emitted during its operation. This study was aimed at developing a noiseless neck suction chamber device that could stimulate the baroreceptors located in the carotid sinus in humans. Methods: A non-invasive device was developed to pressurize the carotid arteries externally. A microcontroller with a computer interface and neck chamber (3D-printed) was used. The anatomical neck chamber was fitted on six healthy, young, asymptomatic participants (5 men; 32±6 yr), who were normotensive, nonsmoking, in sinus rhythm, free of known cardiovascular or metabolic diseases, and not consuming any acute or chronic medications. A suction of -60 mmHg was applied for 5 s, and the corresponding data were recorded. Before each study visit, the participants were instructed to abstain from caffeine, alcohol, and strenuous exercise for 12–24 h. Results: In all the trials, a significant reflex bradycardia (-10 ± 2 bpm) and depressor response (-15 ± 4 mmHg) to neck suction was observed, consistent with the results in the literature. The neck chamber device operated noiselessly (sound pressure level of 34.3 dB) compared to a regular vacuum-cleaner-based system (74.6 dB).